2019
DOI: 10.1177/2158244019865813
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Penetration of Bitcoin: The Role of Psychological Distance and National Culture

Abstract: Previous studies showed that a number of factors play roles in influencing Bitcoin penetration and acceptance, both at country and individual level, such as trust, perceived risk, security threat, perceived benefit, perceived ease of use, as well as macrotechnological and socioeconomic factors. This present study aimed at finding theoretical models at the macro-and microlevels that are able to explain the penetration and acceptance. Study 1 examined hypotheses on the predictive relationship between national cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In the choice of this cryptocurrency the socio-cultural aspects that some studies have shown have a determining role. In particular Abraham et al, 2019 analyzed the factors that influence the degree of penetration and acceptance of bitcoin at various individual and collective levels mainly related to the perception and acceptance of risk, the degree of safety and ease of use. Certainly it cannot be omitted that bitcoins generate negative externalities from an environmental point of view due to the inefficient use of energy sources used for the validation of transactions and are often used for non-transparent operations, criminal and illicit aims.…”
Section: Resultsmentioning
confidence: 99%
“…In the choice of this cryptocurrency the socio-cultural aspects that some studies have shown have a determining role. In particular Abraham et al, 2019 analyzed the factors that influence the degree of penetration and acceptance of bitcoin at various individual and collective levels mainly related to the perception and acceptance of risk, the degree of safety and ease of use. Certainly it cannot be omitted that bitcoins generate negative externalities from an environmental point of view due to the inefficient use of energy sources used for the validation of transactions and are often used for non-transparent operations, criminal and illicit aims.…”
Section: Resultsmentioning
confidence: 99%
“…For example, risks can arise from the decentralized exchange of Bitcoin that is not supported by any institution that should have been responsible for regulating the quality and the transaction of the currency, as stated by Abraham et al [4]. Meanwhile on the wallets sectors, cryptocurrency has a digital program with the use of private and public cryptographic keys management, helping the users to store, send, and receive cryptocurrencies [2].…”
Section: The Phenomenon Of Cryptocurrencymentioning
confidence: 99%
“…Responding to the robust phenomenon of cryptocurrency, there are several reasons that underlie why investment behavior of cryptocurrency users are increasing, especially in the young investors. By using the realm of the sociopsychological aspects, Abraham et al [4] explained that there are some sociopsychological factors that affect individuals to invest in cryptocurrencies.…”
Section: Psychological Factors That Affect Investment Behavior In Cry...mentioning
confidence: 99%
“…Apart from these research, Abraham, Sutiksno, Kurniasih, and Warokka (2019) investigated the influence of psychological distance and country culture on Bitcoin acceptance and penetration. The first part of the study, which looked at the predictive relationship between national cultural orientation and Bitcoin adoption in 60 countries, and the second part, which looked at the predictive power of psychological distances against Bitcoin acceptance in 565 Indonesians, found that individualism, uncertainty avoidance, and long-term orientation are all determinants of Bitcoin adoption.…”
Section: Introductionmentioning
confidence: 99%